A formação do guarda civil metropolitano para o enfrentamento à violência doméstica - Souza, Elza Paulina de (2023)
The present dissertation intends to analyze the relationship between the formation of the Metropolitan Civil Guard of the city of São Paulo and their specific performance in the fight against domestic violence against women and in the fulfillment of protective measures related to the Maria da Penha Law, Federal Law 11.340 of 2006. The focus of the research focuses specifically on the trajectory of the Guardiã Maria da Penha Program of the Metropolitan Civil Guard (GCM), in the period between 2018 and 2022. The research is committed to evaluating and systematizing the process of creating the program and the changes that have occurred. throughout its history, with regard to content, approach and methodology. It aims to outline an overview of the innovations, advances and contradictions that emerged throughout the process. It also seeks to see the results obtained through the use of new forms of contact between victims and care teams. As an urban study, a literature concerning criminology and feminisms will be mobilized; it will also be addressed in this research, with the intention of understanding to what extent this public has specificities and what paths have been indicated by specialists as necessary to break this condition of violence. The overlap between gender violence and structural machismo is evident in the format of the program and its evaluation. As an analysis methodology, the research adopts an empirical approach, in the sense of triangulating the collected information. The research will seek to rely on various sources of evidence, among which stand out public administration documents. In addition, the use of secondary data related to the evaluation of the municipal policy to combat domestic violence will be adopted as consolidated research published on the subject.